Resilience to Global Health Challenges Through Nutritional Gut Microbiome Modulation - Isolauri, Erika; Laitinen, Kirsi (MDPI, 2025)
As the world faces an escalating challenge of non-communicable diseases (NCDs), with phenotypes ranging from allergic chronic immuno-inflammatory diseases to neuropsychiatric disorders, it becomes evident that their seeds are sown during the early stages of life. Furthermore, within only a few decades, human obesity has reached epidemic proportions and now represents the most serious public health challenge of our time. Recent demonstrations that a growing number of these conditions are linked to aberrant gut microbiota composition and function have evoked active scientific interest in host-microbe crosstalk, characterizing and modulating the gut microbiota in at-risk circumstances. These efforts appear particularly justified during the most critical period of developmental plasticity when the child's immune, metabolic, and microbiological constitutions lend themselves to long-term adjustment. Pregnancy and early infancy epitomize an ideal developmental juncture for preventive measures aiming to reduce the risk of NCDs; by promoting the health of pregnant and lactating women today, the health of the next generation(s) may be successfully improved. The perfect tools for this initiative derive from the earliest and most massive source of environmental exposures, namely the microbiome and nutrition, due to their fundamental interactions in the function of the host immune and metabolic maturation.